Studi Kasus Penatalaksanaan Gizi Pada Pasien Anak Dengan Diagnosa Chronic Kidney Disease (CKD) ST V EC Glomerulonephritis Kronis, Multisystem Inflammatory Syndrom In Children (MISC), Hipertensi Terkontrol dan Obesitas di Ruang Gardenia 2 RSUP Prof. DR. I.G.N.G. Ngoerah - Wirasamadi, Ni Luh Partiwi; Zakaria, H.; Tamrin, Abdullah; Hariani, Gusti Ayu Nyoman (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2025)
Chronic Kidney Disease (CKD) in children is a progressive chronic condition that significantly affects their growth, development, and quality of life. This study aims to implement nutritional management for a pediatric patient with stage V CKD caused by chronic glomerulonephritis, accompanied by Multisystem Inflammatory Syndrome in Children (MIS-C), controlled hypertension, and obesity, using the Nutrition Care Process (NCP) approach. The study was conducted as a descriptive observational case study from July 11 to 17, 2025, in the Gardenia Ward of RSUP Prof. Dr. I.G.N.G. Ngoerah. Nutritional intervention was carried out through oral administration of a special renal diet, consisting of three main meals and two snacks per day. The patient's energy requirement was set at 2,289 kcal/day, with a macronutrient distribution of 85.8 grams of protein (15%), 76.3 grams of fat (30%), and 314.7 grams of carbohydrates (55%). Fluid intake was limited to 990 ml/day out of a total requirement of 2,490 ml/day. Micronutrient limits included 1,600 mg sodium, 5,000 mg potassium, 1,250 mg phosphorus, and 15 mg iron per day. Monitoring results showed improvement in nutritional status from obesity to overweight, stable clinical condition, and significantly improved food intake during the intervention period.